Low anterior access single port robotic pyeloplasty in a pediatric patient - Austin Thompson; Kassandra Zaila Ardines; Shelby Harper; Nicolas Soputro; Jihad H. Kaouk; John K. Weaver; Jessica H. Hannick (Urology Video Journal)
Introduction and Objective: Single port robotic surgery may be associated with less pain, faster recovery, and improved cosmesis. Herein we demonstrate that the lower anterior access (LAA) approach to single port robotic pyeloplasty is a safe surgical alternative in conjunction with principles of enhanced recovery after surgery (ERAS) to optimize the management of ureteropelvic junction obstruction (UPJO) in children. Surgical Procedure: Access to the retroperitoneum was gained via a 3.5 cm incision two finger breadths above the superior pubic ramus. A purpose built single port access kit was inserted into the incision after blunt finger dissection. A retroperitoneal robotic dismembered pyeloplasty was performed across a JJ ureteral stent. The patient received an ultrasound-guided transversus abdominis plane block at the conclusion of surgery. Results: Total console time was 95 min. No intraoperative narcotics were given and a total of 3.7 mg oral morphine equivalents was given post-operatively. The patient was discharged the evening of surgery. His left flank pain and hydronephrosis had resolved at follow-up with no complications to date and a single easily concealed scar. Conclusion: The LAA approach to single-port robotic pyeloplasty is a safe alternative that should be offered to pediatric patients with ureteropelvic junction obstruction. This approach may further reduce lengths of stay and the need for opioids while optimizing surgical cosmesis. It may also represent a safer alternative for patients with a history of abdominal surgery.